IMPLEMENTATION OF SAFETY MANAGEMENT SYSTEM HAS A POSITIVE INFLUENCE ON SAFETY CULTURE IN INDONESIAN RAILWAY CONSTRUCTION PROJECTS - hasbi, hariandy; Ramdhan, Doni Hikmat (Universitas Aisyah Pringsewu, 2024)
This study aims to measure the implementation of safety management systems in Indonesian railway construction uses Cooper's reciprocal safety culture model. In addition, it is emphasized that an effective safety management system and a strong management commitment to safety play an important role in improving the safety culture in the railway construction sector. Research analysis tools using confirmatory factor analysis (CFA), data collection through questionnaires distributed to workers in the railway construction sector by measuring three main dimensions of safety culture, namely: workers' perception of safety climate, safety behavior, and safety management system. The results of the analysis show that worker safety behavior, safety climate, and safety management system have a positive and significant influence on safety culture. Good safety behavior, a positive safety climate, and an effective safety management system all contribute to strengthening the safety culture in the field of railway construction. Implementation of a good safety management system, including strict procedures, effective training, and efficient communication, significantly improves worker safety behavior and reduces the risk of work accidents.Keywords: Safety Culture, Safety Climate, Safety Behavior, Safety Management System, Cooper's reciprocal safety culture model.